2017
DOI: 10.2500/ajra.2017.31.4457
|View full text |Cite
|
Sign up to set email alerts
|

Rna Sequencing and Pathway Analysis Identify Tumor Necrosis Factor Alpha Driven Small Proline-Rich Protein Dysregulation in Chronic Rhinosinusitis

Abstract: Background: Chronic rhinosinusitis (CRS) is a heterogeneous inflammatory disorder in which many

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
(49 reference statements)
0
13
0
Order By: Relevance
“…Overall, based on DEGs, 32 pathways (38%) overlap between the upper and lower airways, and 27 pathways were common to all three phenotypes (OM, CRS, and Lower; Supplementary Figure 5; Supplementary Table 5). Notably about half of these 27 pathways that were common in OM, CRS, and Lower also overlap with DEGs identified in previous microarray and RNA-Seq studies (Liu et al, 2004;Kwon et al, 2006;Lee et al, 2006;Payne et al, 2008;Raju et al, 2008;Stankovic et al, 2008;Rostkowska-Nadolska et al, 2011;Klenke et al, 2012;Macias et al, 2013;Wang et al, 2016;Ramakrishnan et al, 2017;Wang et al, 2017;Gao et al, 2018a;Gao et al, 2018b;Kato et al, 2018;Langelier et al, 2018;Ninomiya et al, 2018;Okada et al, 2018;Jovanovic et al, 2019;Walter et al, 2019;Yao et al, 2019). The common pathways from Part 2 RNA-Seq data that were identified in the transcriptome literature are apoptosis, cell adhesion, cell cycle, cell proliferation, chromatin organization/remodeling, Table 6).…”
Section: Genes and Pathways Identified By Rna-seq (Part 2)mentioning
confidence: 72%
See 1 more Smart Citation
“…Overall, based on DEGs, 32 pathways (38%) overlap between the upper and lower airways, and 27 pathways were common to all three phenotypes (OM, CRS, and Lower; Supplementary Figure 5; Supplementary Table 5). Notably about half of these 27 pathways that were common in OM, CRS, and Lower also overlap with DEGs identified in previous microarray and RNA-Seq studies (Liu et al, 2004;Kwon et al, 2006;Lee et al, 2006;Payne et al, 2008;Raju et al, 2008;Stankovic et al, 2008;Rostkowska-Nadolska et al, 2011;Klenke et al, 2012;Macias et al, 2013;Wang et al, 2016;Ramakrishnan et al, 2017;Wang et al, 2017;Gao et al, 2018a;Gao et al, 2018b;Kato et al, 2018;Langelier et al, 2018;Ninomiya et al, 2018;Okada et al, 2018;Jovanovic et al, 2019;Walter et al, 2019;Yao et al, 2019). The common pathways from Part 2 RNA-Seq data that were identified in the transcriptome literature are apoptosis, cell adhesion, cell cycle, cell proliferation, chromatin organization/remodeling, Table 6).…”
Section: Genes and Pathways Identified By Rna-seq (Part 2)mentioning
confidence: 72%
“…Previously, uncinate mucosa tissue from three patients with CRS and four control individuals underwent RNA-Seq (Ramakrishnan et al, 2017). For lung phenotypes, a search of the NCBI Gene Expression Omnibus (GEO) database (http:// www.ncbi.nlm.nih.gov/geo/) did not identify transcriptome data on lower airway tissue biopsies.…”
Section: Rna-seq Data For Crs Ntm and Copdmentioning
confidence: 99%
“…Interestingly, proteins of similar molecular weight were found and may correspond to Nogo-A-F1, Nogo-A-F2, and Nogo-A-FL. Statistics: One-way ANOVA, Dunnett's post hoc test, *P < 0.05; **P < 0.01; ***P < 0.001; † P < 0.0001. retinae, therefore, suggests weaker RGC stress post-injury, perhaps due to TNFα decrease 50 . To further characterize TNFα protein changes, vitreous samples were analyzed by Western Blotting the day following antibody administration (Fig.…”
Section: Nogo-a Antibody Inhibits Monocyte-mediated Inflammation In Tmentioning
confidence: 97%
“…Along with TNFα, Sprr1a is the protein whose gene expression was the most downregulated by 11C7 at 7 days post-NMDA delivery. Interestingly, the expression of Sprr1a could be influenced by TNFα in inflammation 50 . It is thus tempting to propose that Nogo-A-Delta 20/P.cofilin/TNFα/Sprr1a may be a stress signaling pathway mediating chronic RGC dysfunction in the injured retina and that may be reversed by 11C7 treatment.…”
Section: Switch In Microglia and Müller Glia Reaction To Injurymentioning
confidence: 99%
“…Another study that provided fascinating scientific insight was by Ramakrishnan et al 4 and explores the potential causative mechanisms that contribute to the epithelial barrier dysfunction seen in chronic rhinosinusitis. When looking at uncinate tissue specimens from patients with chronic rhinosinusitis and controls, they found that expression levels of two small proline-rich proteins were increased in the mucosal samples from the patients with chronic rhinosinusitis.…”
mentioning
confidence: 99%